SKALA USAHA DAN PELATIHAN AKUNTANSI SYARIAH TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI DI BMT SE- KARESIDENAN PATI (Equilibrium: Jurnal Ekonomi Syariah, 2016)
This study aimed to examine the effect of education managers, company lifespan, scale effort, sharia accounting training on the use of accounting information systems at BMT in ex-Pati residency. This was field research with survey through questionnaires. Samples of this study were the manager of BMT both headquarters and branch offices which actively operate in ex-Pati residency totaling 114 respondents using purposive sampling method. The results showed that managers education influences the use of accounting information systems based on the coeffecience of total effect 0.12. The company lifespan influences the use of accounting information systems based on the coefficience of  total effect 0.19. The business scale influences the use of accounting information systems based on the coefficience of  total effect 0.20. And sharia accounting training affects the use of accounting information systems based on the coefficience of total effect 0.35.